2001
DOI: 10.1128/jvi.75.14.6719-6728.2001
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Cyclization Sequences in Flavivirus RNA Replication

Abstract: A possible role in RNA replication for interactions between conserved complementary (cyclization) sequences in the 5-and 3-terminal regions of Flavivirus RNA was previously suggested but never tested in vivo. Using the M-fold program for RNA secondary-structure predictions, we examined for the first time the base-pairing interactions between the covalently linked 5 genomic region (first ϳ160 nucleotides) and the 3 untranslated region (last ϳ115 nucleotides) for a range of mosquito-borne Flavivirus species. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
346
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(359 citation statements)
references
References 51 publications
11
346
1
1
Order By: Relevance
“…The CS1 (GCATATTGACACCTGGGAAAGAC) and CS2 (GGACTAGAGGTTAGAGGAGACCC) of ROCV are nearly identical to the corresponding conserved sequences among YFV, DENV and JEV (Chambers et al, 1990;Hahn et al, 1987;Khromykh et al, 2001). On the other hand, the 39-terminal sequence of the CS3 of ROCV (CCCCAGGA-GGACTGGGTTTTCAAAGC) is slightly degenerate or different.…”
Section: §-And 3 §-Ncrsmentioning
confidence: 88%
See 2 more Smart Citations
“…The CS1 (GCATATTGACACCTGGGAAAGAC) and CS2 (GGACTAGAGGTTAGAGGAGACCC) of ROCV are nearly identical to the corresponding conserved sequences among YFV, DENV and JEV (Chambers et al, 1990;Hahn et al, 1987;Khromykh et al, 2001). On the other hand, the 39-terminal sequence of the CS3 of ROCV (CCCCAGGA-GGACTGGGTTTTCAAAGC) is slightly degenerate or different.…”
Section: §-And 3 §-Ncrsmentioning
confidence: 88%
“…Moreover, the putative changes in the highly conserved regions related to important biological functions of the flaviviruses (survival and/or pathogenicity) were recognized (Bryant et al, 2005;Khromykh et al, 2001). Khromykh et al (2001) demonstrated that at least one base-pairing between the 59-39 termini, rather than the nucleotide sequences per se, is essential for the replication of viral RNA of the mosquito-borne Kunjin virus, a member of the JEV group, and that more than one pair of cyclization sequences might be involved in the replication of the tick-borne flaviviruses.In terms of CS organization in the 39-NCR, our results revealed a CS3-CS2-RCS2-CS1 pattern for ROCV. This CS organization for ROCV is very similar to but distinct from that of the JEV group viruses (RCS3-CS3-RCS2-CS2-CS1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This 59-CS is actually part of the flavivirus coding sequence. It has been suggested that the flavivirus 59-CS sequence base pairs with CS1 via a longrange RNA interaction (Hahn et al, 1987;Khromykh et al, 2001). This interaction is predicted to result in a 'panhandle'-like structure that is hypothesized to be required for virus replication by modulating virus translation .…”
Section: Discussionmentioning
confidence: 99%
“…2(c) (Gebhard et al, 2011;Villordo & Gamarnik, 2009). In DENV, cyclization is essential for negative-strand synthesis (Alvarez et al, 2005a;Khromykh et al, 2001;Lo et al, 2003), and a balance between both conformations is critical for virus replication (Villordo et al, 2010). DENV genome replication is dependent on activation of viral RdRp via binding 59NCR stem loop SLA and genome cyclization to reposition the activated replication complex at the 39NCR transcription initiation site (Filomatori et al, 2011;Filomatori et al, 2006).…”
Section: Flavivirusesmentioning
confidence: 99%